Pushing the boundaries multiteam systems in research and practice - Rico, Ramón; Shuffler, Marissa L.; Salas, Eduardo (Research on managing groups and teams, 2014)
The latest volume of Research in managing groups and teams focuses on multiteam systems (MTSs), or systems of interdependent teams working toward a shared goal. MTSs have become a growing area of interest in organizational research, primarily due to their growing prominence in organizational settings. However, while MTS implementation is rampant in the field, the majority of research to date has been conducted in laboratory settings, which may not always effectively address the rapidly changing needs of field MTSs. This book brings current, real world MTS issues and problems to the forefront while highlighting existing research across disciplines which may help to address these issues. The volume takes a unique approach in addressing the practical and research needs of understanding multiteam systems by highlighting real world issues via case studies presented by practitioners. Themes highlighted in terms of both practical issues and future research needs include the development and composition of MTSs, critical processes such as leadership and communication, and outcomes of both successful and unsuccessful MTSs.